Wilderness Pilgrimage in the Midst of Pandemic: Appalachian Trail in the Wake of Trail Closure and Infrastructure Shutdowns - Kip Redick (Ad Limina)
This paper presents research conducted both on the Appalachian Trail and through reading hiker blogs written between March and June of 2020. The Trail research happened between Beauty Spot, Tennessee and Mountain Harbor Hostel, Tennessee, about 50 miles. Both Virginia and North Carolina had restricted access to the Appalachian Trail, but Tennessee was open. I engaged in ethnographic fieldwork amongst long-distance hikers still in the midst of their trek. In addition, I interviewed a hostel owner. In late June, after Virginia opened access to the Appalachian Trail, I traveled to Damascus and conducted more interviews. I also accessed hiker blogs, gathering first-hand accounts of experiences related to the Appalachian Trail during the initial stage of the pandemic. This paper investigates the social and environmental forces that shaped pilgrim/hiker experiences during the pandemic.